E74‐like ETS transcription factor 3 expression and regulation in human intervertebral disc - María González‐Rodríguez; Djedjiga Ait Eldjoudi; Alfonso Cordero‐Barreal; Mariam Farrag; María Varela‐García; Clara Ruiz‐Fernández; Carlos Torrijos‐Pulpón; Francisca Lago; Lucía García‐Caballero; Yousof Farrag; Javier Conde‐Aranda; Jesus Pino; et al. (JOR Spine)
Abstract Background Intervertebral disc degeneration (IVDD) is one of the main causes of chronic low back pain. The degenerative process is often initiated by an imbalance between catabolic and anabolic pathways. Despite the large socio‐economic impact, the initiation and progress of disc degeneration are poorly understood. Although intervertebral disc (IVD) and articular joint are not identical, their degenerative roads are remarkably similar. We, and another authors, previously demonstrated that E‐74‐like factor 3 (ELF3), a transcription factor induced by inflammatory mediators in various cell types including chondrocytes, is a central contributing factor for cartilage degradation. Thus, we aim to explore, for the first time, the expression, modulation, and the role of ELF3 in human IVD cells. Methods The presence of ELF3 in healthy and degenerated IVD tissues was initially determined by immunohistochemistry in annulus fibrosus (AF) and nucleus pulposus (NP). mRNA and protein expression were measured, respectively, by RT‐qPCR and Western blot in AF and NP IVD cells harvested from healthy individuals and IVDD patients. Overexpression of ELF3 was performed by transfection of AF IVDD cells with pESE‐1: ELF3 expression vector or pCI: empty vector. Results Our results unveiled, for the first time, the expression of ELF3 in IVD tissues. ELF3 is notably upregulated in degenerated tissues compared to those from healthy patients. In addition, the stimulation of IVDD AF cells with various proinflammatory stimuli, showed marked increase in both mRNA and protein expression of ELF3. ELF3 overexpression in AF IVDD cells resulted in the upregulation of proinflammatory and catabolic genes such as PTGS2, NOS2, LCN2, IL‐6, MMP13, and ADAMTS‐5; whereas, ELF3 silencing resulted in the opposite results. Conclusions Our results support a novel role for ELF3 as a pro‐inflammatory and pro‐catabolic transcriptional mediator, whose targeting in IVD tissues might be of potential therapeutic relevance in disc degeneration.